Investigation of dynamic cable-deck interaction in a physical model of a cable-stayed bridge. Part II : seismic response - Elsa Caetano (2000)
The present paper describes an investigation of the effect of dynamic cable interaction with the deck and towers in the seismic response of a cable-stayed bridge. This study involved shaking table tests performed on a physical model of Jindo bridge, in order to validate two alternative numerical models, which differ in terms of consideration of coupled cable/deck and towers modes. The response to artificial accelerograms was calculated and correlated with measured data. Additional numerical simulations are presented in order to clarify the role that cables play in the attenuation or amplification of the structural response. It was found that the cable interfer-ence with global oscillations may cause a decrease of the bridge response. However, this sys-tem damping may not develop in the case where a narrow band excitation is applied, causing large amplitude of vibrations of some cables, with significant nonlinearity, and inducing higher order modes.